Effectiveness Test of Red Spinach Leaf Extract (Amarathus Tricolor L) as a Substitute for Crystal Violet in Gram Staining of Staphylococcus Aureus Bacteria Morphology - Diastari Damayanti; Telambanua, Arniat Christiani (International Health Sciences Journal, 2025)
Gram staining is the most common procedure used to identify bacterial morphology, using crystal violet as the primary dye. However, crystal violet is a synthetic dye that has toxic effects on the environment and health. The purpose of this study was to test the effectiveness of red spinach leaf extract (Amaranthus tricolor L) as an alternative natural dye to replace crystal violet in Gram staining of Staphylococcus aureus bacteria morphology. This type of research is a laboratory experiment with a post-test group control design with samples of Staphylococcus aureus bacterial colonies and red spinach leaf extract with concentrations of 20%, 40%, 60%, 80%, and 100%. Bacterial morphology was observed based on color intensity and clarity of cell shape. The results showed that red spinach leaf extract with a concentration of 100% gave very good morphological results and approached staining using crystal violet. The results of the Kruskal-Wallis test showed a significance value of 0.009 (p <0.05), indicating that there is a significant difference between the concentration groups and the color quality of the Staphylococcus aureus bacteria. This study concludes that red spinach leaf extract is effective as an alternative natural dye to replace crystal violet in Gram staining of Staphylococcus aureus bacteria. Suggestions for further researchers are to conduct further research on the use of natural dyes that can be used as natural dyes to replace crystal violet, which are able to color bacterial morphology in Gram staining.